Airport branding and stakeholders collaborative communication - Hanifah, Karina Putri; Perbawasari, Susie; Hafiar, Hanny (Bricolage : Jurnal Magister Ilmu Komunikasi, 2025)
This research examines how stakeholders collaboration affects airport branding by exploring the role of cooperative efforts in shaping brand identity and reputation. It investigates how transparent communication, alignment with stakeholders expectations, and engagement with various groups-such as investors, consumers, local communities, and business partners aero and non-aero as well as local governments contribute to developing a cohesive and competitive branding strategy. This research utilizes a bibliometric approach, which aims to provide an overview of the global trends of this topic, as well as identify the dominance of the most influential authors, co-authors, institutions, countries, and publications in this field. The data was obtained through the Scopus database through a relevant keyword search that resulted in 639 articles, and then data processing and analysis were carried out through the tools VOS Viewer, RStudio Biblioshiny, and ScientoPy. Modern branding today does not just rely on unilateral communication but becomes more cooperative by involving various stakeholders. However, there are limited studies that provide a comprehensive overview of this field. The findings show that branding and stakeholders collaboration are increasingly important in shaping corporate identity, enhancing reputation and fostering long-term sustainable relationships. Some of the dominant and influential authors and institutions in research in this area are from Europe, the United States, and Australia, but contributions from developing countries are still minimal. This study recommends further in-depth research in developing countries, including Indonesia, given the great potential in airport branding development that can be done through stakeholders collaboration with a holistic approach that includes transparent communication, utilization of local cultural narratives as differentiating elements, and integration of sustainability values to build a relevant and globally competitive brand image.